2017
DOI: 10.1007/s40264-017-0619-x
|View full text |Cite
|
Sign up to set email alerts
|

The RIMES Statement: A Checklist to Assess the Quality of Studies Evaluating Risk Minimization Programs for Medicinal Products

Abstract: IntroductionPharmaceutical risk minimization programs involve interventions designed to support safe and appropriate use of medicines. Currently, information regarding the evaluation of these programs is not publicly reported in a standardized and transparent manner. To address this gap, we developed and piloted a quality reporting checklist entitled the Reporting recommendations Intended for pharmaceutical risk Minimization Evaluation Studies (RIMES).MethodsChecklist development was guided by three sources: (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The quality of RMM effectiveness studies will be supported with EU good pharmacovigilance practices currently under revision by PRAC. A standard to ensure high-quality reporting of such studies, the RIMES statement, has already become available [ 40 ] and its use will be encouraged in the revised EU good pharmacovigilance practices.…”
Section: Resultsmentioning
confidence: 99%
“…The quality of RMM effectiveness studies will be supported with EU good pharmacovigilance practices currently under revision by PRAC. A standard to ensure high-quality reporting of such studies, the RIMES statement, has already become available [ 40 ] and its use will be encouraged in the revised EU good pharmacovigilance practices.…”
Section: Resultsmentioning
confidence: 99%
“…Of note, our study examined the type and quantity of REMS assessment measures from the original approval; however, it did not assess the rigor of proposed study designs nor the quality of their reports. Reporting standards for risk minimization communication and program evaluation have been described by members of the International Society for Pharmacoepidemiology (40). A systematic review of the published literature on pharmaceutical risk minimization evaluation found limited use of conceptual frameworks guiding process and outcome measurement selection and program design and implementation (41).…”
Section: Discussionmentioning
confidence: 99%
“…A two‐wave online survey study was conducted to evaluate the effectiveness and improvement of the updated SIP, according to PASS GVP module VIII, best practices for the conduct and reporting of survey studies, and research papers in the field . Wave (W) 1 was carried out preimplementation of the updated SIP and W2 after distribution of the updated SIP in the participating countries.…”
Section: Methodsmentioning
confidence: 99%